Effects of postmortem aging period and blade tenderization on sensory traits of beef steaks - George-Evins, C.D.; Unruh, John A.; Marsden, James L.; Kastner, Curtis L. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
We used 54 strip loins, 54 top sirloin butts, and 54 inside rounds, all USDA Choice grade, to determine the influence of different postmortem aging periods and blade tenderization passes on sensory panel traits. Cuts were aged for 7, 14, or 21 days and not tenderized (0X) or blade tenderized one (1X) or two (2X) times. All steaks were cooked to 160°F internally, and samples were evaluated by a trained sensory panel for flavor intensity, juiciness, myofibrillar tenderness, connective tissue amount, and overall tenderness. Both longer aging periods and blade tenderization passes improved tenderness of strip loin and top sirloin butt steaks without affecting either flavor or juiciness, but did not affect tenderness of top round steaks. Therefore, meat purveyors should use these technologies to improve tenderness and consistency of strip loin and top sirloin butt steaks.
Keywords: Beef; Sensory panel; Blade tenderization; Aging; Steak cuts